SOME PROBLEMS OF PROTECTING THE RIGHTS OF CHILDREN VICTIMS OF VIOLENCE IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2025)
The economic crisis and emergency situations of any state lead to the collapse of the institution of the family and spiritual values. As you know, the covid pandemic, which swept the whole world in 2019, led to instability of the global economy, a decrease in the standard of living and social stratification of people, and a change in the cultural life of the younger generation. As a result, the legal, economic, and moral instability of the population contributed to the breakdown of family relations and the relationship between parents and children of spouses. There are more and more aggressors in society, and adults are increasingly showing physical, sexual, and emotional violence and child abuse.Violence and child abuse have become one of the world's problems. Violence not only threatens the life and health of a child, but also adversely affects the future of the State as a whole. The level of development of the State is assessed based on its attitude to social groups. Currently, about 1 billion children per year become victims of violence. The majority of victims of violence are children from low-income, neglected families.  A child easily becomes a victim of violence due to self-doubt and age. To establish a nonviolent society, punishing criminals is not enough, the crime must not remain hidden, the struggle must be waged openly, for this every citizen must not tolerate violence.The authors, relying on the scientific works of scientists, judicial practice and decisions of the Supreme Court, pay attention to measures to curb violence against children and the procedure for imposing punishments. Certain types of responsibility for child abuse were studied. The authors recognize the age of criminal responsibility for crimes of violence, bullying, and abuse of minors as 14 years old and have scientifically substantiated it. It is also proposed to supplement the Family and Civil Procedure Codes with norms providing for the procedural status of children, that is, a minor plaintiff, the right to go to court and free legal assistance from a lawyer, and the obligation to prove a violation of the rights of minors.  As a result of the research, the author's definition of the concept of «child abuse» is given.The scientific article was prepared within the framework of program-targeted funding for scientific and (or) scientific and technical programs for 2023-2025, aimed at implementing the project IRN BR 27882414 “Program for the support and rehabilitation of child victims of violence: practical implementation of a network of modular resource centers”, financed by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan.Keywords: child, child rights, victim of violence, bullying, child abuse, criminal liability, domestic violence.